Central ai lhe seed rice nematode Apho/enchoides besseyi. - Silveira, Salima G.P. Da; Curi, Sérgio M.; Leite, Norberto; Camargo, Otávio B. De A.; Neto, Francisco Brignani; Arruda, Hermano V. De (Pesquisa Agropecuaria Brasileira, 2013)
Six triale were carried oul nt Lorena and Pindamonhangaba, SP, Brazil, to study lhe confrol of the rice nematode Aphe/encho ides besseyi Christie 1942, for irrigated conditons. Some chemicals and one thernial treatment were elteclive in decreasing nematode density nevertheless, there was no associailon with yield increases. The cultivars IR 841, IAC 435, IAC 120 and IAC 899 were very tolerant to nematode with yields prominence 01 lAC 899.